Molecular diagnosis of dystrophinopathies using a multi-technique analisis algorithm - Luce, Leonela N. (2013)
Dystrophinopathies are X-linked recessive neuromuscular diseases caused by mutations in the dystrophin gene. In this study we aimed to detect mutations within the dystrophin gene in DMD patients, to determine the carrier status of women, and to perform a prenatal diagnosis. Methods: We analyzed 17 individuals from 2 unrelated families with a history of DMD. We used multiplex PCR, multiplex ligation-dependent probe amplification (MLPA), and short tandem-repeat (STR) segregation analysis to accurately detect and characterize the mutations and to identify the at-risk haplotype. Results: The selected methodology allowed for the characterization of 2 single-exon out-of-frame deletions in the affected patients. Nine of 13 women and a fetus were excluded from being carriers. Three recombination events were found and suggested that germline mosaicism had occurred in both families. Conclusions: This methodology proved to be efficient for characterizing the disease-causing mutation in affected individuals and for assessing the carrier status in healthy relatives. These findings helped inform precise genetic counseling and contributed to characterization of the disease in the Argentine population.